Modelagem e simulação de colunas de destilação reativa - Steffen, Vilmar (2010)
Reactive distillation is the combination of chemical reaction and separation by distillation in only one equipment (these processes generally take place separately and in sequence in the industries of chemical processes). The integration of these two operations can increase the global performance of the production line. Thus, becomes necessary a previous study of the possibility to join these processes in a single equipment. The tool to start the study on a new process or the optimization of a process in operation is the modeling and simulation. The mathematical models for reactive distillation columns are constituted of a system of non linear equations. Several algorithms for simulation of distillation columns in steady state with different degrees of precision and consequently of difficulties were developed in the last decades. However, these algorithms don't supply a procedure to obtain the initial guesses, that are fundamental for the convergence of the method used to solve the system of non linear equations. In this work was developed an algorithm for the solution of mathematical model that describes the reactive distillation process in columns that operates in steady state. In the developed algorithm was defined a procedure to obtain reasonable initial guesses that facilitates the convergence of the method. The great majority of methods for simulation of distillation column in stead-state solve all the equations simultaneously by a system of non linear equations solution s method. In this work was developed an algorithm step-by-step, to facilitate it s understanding, where the system of non linear equations solution s method is necessary just for the group of equations that models the chemical reactions, so that, two system of non linear equations solution s methods were used, the method of Broyden (a variation of the Newton-Raphson s method) and the homotopy continuation method (or homotopy). The mathematical model was obtained from mass balances, energy balances, sum equations, phase equilibrium and chemical equilibrium or chemical kinetics. The modeling of phase equilibrium is rigorous by means of the calculation of activity and fugacity coefficients, the modeling of the thermal effects is also rigorous by means of the calculation of the residual and excess enthalpies. The developed algorithm was evaluated from examples of the literature and in all cases the obtained results were similar to those found in the literature.